PERTUMBUHAN DAN PRODUKSI KACANG TANAH ( Arachis hypogaea L.) PADA BEBERAPA PENGOLAHAN TANAH INSEPTISOL DAN PEMBERIANPUPUK KASCING - Muhammad Rizqi Habiby; Sengli Damanik; Jonathan Ginting (Jurnal Agroekoteknologi, 2013)
Peanut is one of the source of protein for human foods. Production of peanutscan be increase by land cultivation and giving vermicompost. This research aimed toevaluate the effect of land cultivation and giving vermicompost for growth andproduction of peanuts. The study was conducted in Tanjung Sari, Kecamatan MedanSelayang. This research used split plot design, with two factors. First factor is landcultivation with 4 levels (traditional tillage with two stage of cultivation, traditionaltillage with one stage of cultivation, minimum tillage, and no-tillage).The secondfactor is the ratio of vermicompost and chemical fertilizers, whith 5 levels(chemical 100%,vermicompost 100%, vermicompost 75% + chemical fertilizer25%, vermicompost 50% + chemical fertilizer 50%, and vermicompost 25% +chemical fertilizer 75%. The result showed that land cultivation significantlyaffected the parameters the number of ginofor 2 and 3 month after planting(MAP), the number of filled pod, 100 seed weigth, production per sample andproduction per plot. The ratio of vermicompost and chemical fertilizerssignificantly affected the parameters of the number of branch 1 and 2 MAP. Theinteraction between land cultivation and the ratio of vermicompost and chemicalfertilizers did not significantly affected for all parameters.Keywords : land cultivation, vermicompost, peanuts.